2012
DOI: 10.3390/molecules17033243
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability and Biocompatibility Study of Poly(Chitosan-g-lactic Acid) Scaffolds

Abstract: A biodegradable, biocompatible poly(chitosan-g-lactic acid) (PCLA) scaffold was prepared and evaluated in vitro and in vivo. The PCLA scaffold was obtained by grafting lactic acid (LA) onto the amino groups on chitosan (CS) without a catalyst. The PCLA scaffolds were characterized by Fourier Transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The biodegradabilty was determined by mass loss in vitro, and degradation in vivo as a function of feed ratio of LA/CS. Bone marrow mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 37 publications
4
53
0
Order By: Relevance
“…Moreover, they can be further modified. For example, the DD can be lowered by deacetylation (Zhang and Cui, 2012) and MW can be lowered by acidic depolymerisation (Sorlier et al, 2001). In medical and pharmaceutical applications, chitosan is used as a component in hydrogels.…”
Section: Modifications Of Chitosanmentioning
confidence: 99%
“…Moreover, they can be further modified. For example, the DD can be lowered by deacetylation (Zhang and Cui, 2012) and MW can be lowered by acidic depolymerisation (Sorlier et al, 2001). In medical and pharmaceutical applications, chitosan is used as a component in hydrogels.…”
Section: Modifications Of Chitosanmentioning
confidence: 99%
“…However, due to its low mechanical properties [1,22], it is necessary to combine it with other synthetic or natural polymers. Some investigations about PLA-chitosan composites are described below.…”
Section: Introductionmentioning
confidence: 99%
“…[148] The work of Z. Zhang and H. Cui showed that chitosan with lactic acid (PCLA) combined via the freeze drying technique resulted in a scaffold with better histocompatibility properties for BMSC than each material by itself. [149] …”
Section: D Cell Culture Techniquesmentioning
confidence: 99%